PERSEPSI PESERTA DIDIK TERHADAP PENGGUNAAN ARTIFICIAL INTELIGENCE (AI) DALAM PEMBELAJARAN IPS DI KELAS IX UPT SPF SMP NEGERI 24 MAKASSAR - Nurshalati Urfa; Rusdi; Shasliani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine : 1) An overview of the use of Artificial Intelligence (AI) in social studies learning in grade IX at UPT SPF SMPN 24 Makassar; 2) Students’ perceptions of Artificial Intelligence (AI) regarding its application in Social Studies Learning; 3) The form of student statisfaction with the use of Artificial Intelligence (AI) in suppoting the ideal Social Studies learning process in grade IX at UPT SPF SMPN 24 Makassar. This research employed a descriptive qualitative approach. Data collection techniques were conducted through in-depth interviews with several Grade IX students at UPT SPF SMPN 24 Makassar as the primary respondents, supplemented by documentation. The data obtained were analyzed through data reduction, data display, and conclusion drawing and verification to produce accurate findings.The results of this study indicate that : 1) the overview of Artificial Intelligence (AI) usage in Grade IX at UPT SPF SMPN 24 Makassar shows that AI functions as a flexible assistant capable of tailoring materials to students' learning styles, thereby increasing independent learning initiatives both at school and at home. 2) regarding students' perceptions, the use of AI applications such as ChatGPT, Gemini, and Cici is regarded as an essential tool for simplifying their understanding; despite finding them helpful, students consistently perform cross- verification of the information provided to avoid data inaccuracies. 3) the form of student satisfaction in creating an ideal Social Studies learning process stems from the ease of information access and the time efficiency provided by AI, which allows students to focus more on deepening their understanding and engaging in active classroom discussions.